Evaluasi Reklamasi Laut PT Timah Tbk Program Artificial Reef Di Perairan Rebo Kabupaten Bangka - Rahendra, Rahendra; Toha, M. Taufik; Yusuf, Maulana (Universitas Bangka Belitung, 2024)
This study aims to evaluate the PT TIMAH Tbk sea reclamation program, specifically the artificial reef program. The research was conducted from March to July 2024 at the artificial reef module sinking locations for the Obligatory Years of 2019, 2021, and 2023. The fish data collection method used a modification of the Belt Transect. The biomass calculation method was modified by adding several fish families that are economically valuable target fish. The location of the 2021 Obligatory Year artificial reef modules had the highest number of fish species (40 species), the highest H' value (3.20), and the heaviest biomass (2,908.80 kg/ha). The range of diversity values at all locations was between 1.80-3.20, falling under the criteria of